Beyond Foucault and Post-Panoptic Theories: New Perspectives on China's Surveillance Mechanisms in East Turkestan - Oztig, Lacin Idil; Karluk, Abdurresit Celil (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
Surveillance is as old as human history. In pre-modern times, it mostly took place through spies, informants, and guards. In modern times, it became a systematised practice conducted through bureaucratic structures. Foucault's panopticism explains how surveillance shapes modern societies by turning individuals into self-disciplined subjects. Today, an array of technologies - including algorithms, sensors, satellites, biometric devices, and DNA analysis - is increasingly used for surveillance purposes. The rapid evolution and expansion of these practices, driven by advanced technology, have given rise to new concepts such as 'control society', 'surveillance-oriented societies', 'modulatory control', 'liquid surveillance', 'dataveillance', and many others. We argue that the idiosyncratic surveillance practices employed by China bring a paradigm shift in surveillance studies, as they cannot be fully explained by panoptic and post-panoptic theories of surveillance. Our research is grounded in the firsthand experiences of Uyghurs subjected to China's high-tech surveillance in East Turkestan, collected through approximately 500 surveys, 21 in-depth interviews, and two focus group discussions. Our respondents reveal that China's use of advanced technology infiltrates every facet of social and private life in East Turkestan, compelling the residents to engage in self-discipline not only in the public sphere, but also in their private sphere, extending into their houses and vehicles, family and neighbourly relations, and the ways they interact with technology. China's practices, which we call 'techno-panoptic governance', have moved to extremes in surveilling, disciplining, and manipulating individuals on a granular level. This type of governance is designed to achieve a complete erasure of privacy and individual agency by strategically leveraging technology. Its objective is to manipulate and disrupt individuals' everyday reality, driving them into a state of constant anxiety and paranoia. Under this system, individuals are compelled to perceive and treat their everyday lives as mere data that could alert state authorities at any moment and live in a state-imposed reality.
Keywords: HUMAN-RIGHTS; INTEGRITY; SECURITY; Geography; Government & Law